Therapeutic value in oncology. Patients' caregivers' and professionals' perspective - Arrighi, Emilia; Jovell, Albert J.; Navarro, María Dolores (Psicooncología, 2010)
Objective: The aim of the study is to explore if cancer patients actively participate in their care and are involved in treatment decisions. Method: 4 focus groups were organized for a total of 29 participants. One group with patients older than 63 years old, one group with patients younger than 63 years old and one group with caregivers. Moreover, one group was held with the participation of oncologists. Results: Participants have identified the need to receive clear information about treatment options, besides professionals’ advice and experience. Communication skills must be given to professionals; moreover patients need a referent who can accompany them during making decision process. Conclusions: Patients are taking new roles, are more participatory and want to assume more responsibilities about clinical decisions. Patients have a right to understand their illness, prognosis and treatment options. More training programs for physicians are need in order to tailor treatment options to patients’ preferences and needs.
Keywords: Therapeutic preferentes; Cancer patients; Making decision process